Bubble Up Induced Graphene Microspheres for Engineering Capacitive Energy Storage. Issue 16 (25th February 2023) - Li, Xiangming; Zheng, Qinwen; Li, Congming; Liu, Gangqiang; Yang, Qingzhen; Wang, Yingche; Sun, Pengcheng; Tian, Hongmiao; Wang, Chunhui; Chen, Xiaoliang; Shao, Jinyou
Abstract: Translating the material merits of graphene to practical supercapacitor devices is critical for promoting capacitive energy storage, but is challenging due to the limited scalability in fabricating high‐performance graphene electrode films. Here, we demonstrate a method for fabricating graphene microsphere films, formed by the bubble‐induced destruction and agglomeration of the self‐assembled toplayer of mixed graphene oxide and exfoliated graphene over an adequately heated solution. The microspheres have compact, randomly distributed graphene flakes, endowing the films with a high bulk density (0.92 g cm −3 ) and ion conductivity to allow ultrahigh charge/discharge current densities of up to 1, 000 A g −1 in an ionic liquid. The stack cell with an areal mass loading of 10 mg cm −2 exhibits an excellent energy density of 83.4 Wh L −1, superior to the state‐of‐the‐art carbon‐based supercapacitors, and approaching that of lead‐acid batteries. More importantly, a meter‐scale film is fabricated within half a minute by a developed roll‐to‐roll process, demonstrating the enormous potential of these films in the industrial manufacturing of supercapacitors. Furthermore, the film electrode is infilled with an ionogel electrolyte and assembled into an all‐solid‐state, flexible device with durable flexibility and multiple optional outputs, demonstrating the potential of these supercapacitors for powering flexible electronic devices. Abstract : Bubble up of graphene solution enables the formation of graphene microspheres which have the randomly and compactly distributed graphene flakes, resulting in high ion conductivity and efficient utilization of surface area. The microsphere graphene film can be fabricated at meter scale, and permits stack supercapacitors to deliver high energy density of 83.4 Wh L −1, promising large‐scale storage of capacitive energy.